EVALUASI PEMBELAJARAN MAHASISWA KEPERAWATAN: SEBUAH TINJAUAN - Wulandari, Sarah K.; Nuryanto, I Kadek (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p11, 2023)
The achievement of learning outcomes in tertiary institutions has benchmarks that must be relevant to the industrial world. Active involvement of students in the learning process and the desire to achieve competence according to learning outcomes needs to be facilitated by continuous planning and evaluation. The aim of the current study was to evaluate clinical practice learning satisfaction in nursing students. This research is a descriptive analysis with cross sectional design. The instrument used is the Educational Practices Questionnaire-C (EPQ-C) questionnaire used for self-evaluation learning evaluation variables with 22 statement items with modification. The sample of this study were 78 nursing students using a non-probability technique, namely total sampling. The results of this study indicate that the questionnaire used was reliable with Cronbach`s Alpha 0,77.  The results shown respondents were in the satisfied category as much as 51,2% (40 people). The conclusion in this study is that most students express satisfaction with the clinical learning process that takes place during their education period. However, several assessment items need to get attention so that they can be used as indicators in improving the learning process for students, especially nursing. So that learning satisfaction becomes better and competence achievement is more optimal.